Prominent members of the human gut microbiota express endo-acting O-glycanases to initiate mucin breakdown - Lucy I. Crouch (Nature Portfolio, 2020)
Epithelial cells that line the gut secrete complex glycoproteins that form a mucus layer to protect the gut wall from enteric pathogens. Here, the authors provide a comprehensive characterisation of endo-acting glycoside hydrolases expressed by mucin-degrading members of the microbiome that are able to cleave the O-glycan chains of a range of different animal and human mucins.